Modelagem dos vetores de mudança na paisagem no bioma Cerrado - Thiago Carvalho de Lima (2013)
The Cerrado stands out as the second largest Brazils biome and presents a priceless and unique biological complexity, being identified as a global biodiversity hotspot (Myers et al, 2000). Nevertheless, the biome has been disorderly occupied, mainly due to agricultural expansion. Considering that there are environmental, physical and / or social variables correlated with the dynamics of Cerrado occupation, this study aimed to obtain an econometric model to determine the drivers of deforestation and regeneration by municipality of Cerrado biome from 2002 to 2009. Furthermore, simulations were performed annually until 2050 to test the behavior of the spatial model when term projections above those already monitored were used. In the first part of the study, an econometric model was selected to estimate deforestation or regeneration rates. This model was calibrated in GEODA with Agricultural Census data (IBGE 1995, 2006), obtaining an auto-regression spatial model with an error term that was integrated to DINAMICA EGO software in which the amount of changes were calculated by municipality and spatially allocated. In the simulation, totaling 41 iterations (2009 to 2050), the model presented a loss of 14,237,884.5 ha of forest (approximately 6.034% of deforestation in the period or annual deforestation rate of 0.16%) and a regeneration of 18537264.707 ha of forest (annual regeneration rate of 0.79%). The model showed a trend of decreasing in deforestation annual rates of Cerrado, which can be seen in IBAMA / MMA / UNDP reports when comparing the rates of 2007-2008 with 2008-2009, 3% and 0.37, respectively. This trend that regeneration overlaps deforestation may indicate a forest transition occurring in the biome. Continuous monitoring, in regeneration areas, may provide more consistent data allowing a better fit of the model that can be used as a tool for planning conservation actions in the biome.